PROFIL RASULULLAH SHALALLAHU ‘ALAIHI WASALLAM SEBAGAI KONSELOR IDEAL DAN KONSTRIBUSI TERHADAP PEMBENTUKAN KONSELOR PROFESIONAL - Ahmad Burhanuddin; Lilis Karlina; Sawaluddin Siregar (Yayasan Baitul Hikmah al-Zain, 2025)
A counselor is a profession held by someone who has expertise in the field of counseling services. A counselor is required to be an ideal and professional counselor. Nowadays, there are many counselors who experience failure in counseling because of the quality of the counselee and the quality of the counselor. The study in this research applied descriptive methods. Specifically, with qualitative descriptions. In the sense that the author does not include any numbers that support qualitative research. Meanwhile, the aim of this research is to determine the profile of Rasulullah Shalallahu 'Alaihi Wasallam as an ideal counselor and his contribution to the formation of professional counselors. The character of Rasulullah sallallaahu alaihi wasallam as an ideal counselor has 4 characteristics, namely the Siddiq characteristic, the tabligh characteristic, the trustworthy characteristic, and the fathanah characteristic. The two contributions of the profile of Rasulullah sallallaahu alaihi wasallam as an ideal counselor for the formation of the character of a professional counselor include 1. Having faith and piety, 2. Carrying out good deeds, 3. Advising each other to obey the truth, and 4. Advising each other to maintain patience. The counseling carried out by Rasulullah did not deviate much from Islamic religious law and Allah's law. It is hoped that the absorption of personality values ​​through the personality of the Prophet sallallaahu alaihi wasallam can perfect the counselor's personality values ​​so that they can form ideal and professional personal characteristics for prospective counselors.